2007
DOI: 10.1177/0961203307081421
|View full text |Cite
|
Sign up to set email alerts
|

Unusual neurologic manifestations (I): Parkinsonism in juvenile SLE

Abstract: A girl with neuropsychiatric lupus demonstrated Parkinsonian features soon after commencing risperidone. The single photon emission computed tomography scan showed hyperperfusion of the basal ganglia. Symptoms abated with the addition of dopaminergic agents to immunosuppressive therapy. The literature on juvenile Parkinsonism in lupus has been reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 18 publications
1
30
2
1
Order By: Relevance
“…Cerebral hyperperfusion in SLE has been reported previously, but only in the basal ganglia of SLE patients with Parkinsonian syndrome using relative measures of perfusion with SPECT (35, 36). However, in a study that included at least one patient with SLE, quantitative PET was used to observe higher CBF throughout the brain of patients with renal disease relative to healthy control subjects (24).…”
Section: Discussionmentioning
confidence: 82%
“…Cerebral hyperperfusion in SLE has been reported previously, but only in the basal ganglia of SLE patients with Parkinsonian syndrome using relative measures of perfusion with SPECT (35, 36). However, in a study that included at least one patient with SLE, quantitative PET was used to observe higher CBF throughout the brain of patients with renal disease relative to healthy control subjects (24).…”
Section: Discussionmentioning
confidence: 82%
“…Nevertheless, the unique observational data of the present study obtained by noninvasive transcranial Doppler support our recent report of increased cerebral blood flow in SLE using other methodologies (30). Despite the widespread reports of heterogeneous hypoperfusion in NPSLE, cerebral hyperperfusion in SLE has been noted in a number of prior reports using single photon emission tomography (SPECT), positron emission tomography (PET), or magnetic resonance perfusion-weighted imaging (MRPWI) (3032). Hyperperfusion and altered vascular tone also have been reported in other neurological disorders, including stroke (33), occlusive sickle cell disease (34), transient ischemic attack (35) seizures and epilepsy (36), traumatic brain injury (37), metabolic brain disease (38), and migraine (39).…”
Section: Discussionmentioning
confidence: 99%
“…Improvements have been reported in those patients treated with combination of steroids and cyclophosphamide, with or without antiparkinsonian drugs. 10 In two cases, intravenous injection of immunoglobulins appeared to be effective after methylprednisolone and cyclophosphamide failed. 11 Intrathecal injection of MTX plus DXM, which was assumed to enhance 21 To our knowledge, our patient was the first NPSLE patient with parkinsonism reported to accept intrathecal injection of MTX plus DXM and obtain a satisfactory outcome.…”
Section: Discussionmentioning
confidence: 95%
“…3 Since then, only about 30 NPSLE cases with parkinsonism have been reported to date (Table 1). [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Autoantibodies and immune-mediated vasculopathy was suggested in the pathogenesis of parkinsonism in NPSLE. 20 Kunas et al 4 found antibodies to dopaminergic cells in serum from the NPSLE patients manifested with parkinsonism.…”
Section: Discussionmentioning
confidence: 99%